Investasi Daerah dalam Teori Modernisasi - Dodik Wahyono (LP2M IAI Nazhatut Thullab Sampang, 2021)
This study aims to determine regional investment according to modernization theory. Qualitative descriptive method is the method used in this research with literature study as the data collection. The results of the study are that: 1) it is hoped that the policy can encourage local governments to make regulations that accommodate investors, 2) investment is a concept of modernization theory, which is very relevant when used to view or analyze the existence of regional bond policies or policies for so investors. foreign or domestic investors, and 3) inter-regional cooperation is needed to reduce inter-regional and regional potentials.